2019
DOI: 10.1523/jneurosci.1657-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal BC RNA Transport Impairments Caused by Systemic Lupus Erythematosus Autoantibodies

Abstract: The etiology of the autoimmune disorder systemic lupus erythematosus (SLE) remains poorly understood. In neuropsychiatric SLE (NPSLE), autoimmune responses against neural self-antigens find expression in neurological and cognitive alterations. SLE autoantibodies often target nucleic acids, including RNAs and specifically RNA domains with higher-order structural content. We report that autoantibodies directed against neuronal regulatory brain cytoplasmic (BC) RNAs were generated in a subset of SLE patients. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 79 publications
(235 reference statements)
1
24
0
Order By: Relevance
“…Muslimov and colleagues recently reported that the mislocalization of BC RNAs is also associated with SLE [38]. Researchers confirmed the production of antibodies that recognize BC200 RNA in SLE patients and named them anti-BC abs.…”
Section: Neuronal Diseases Related To Bc Rnasmentioning
confidence: 94%
See 2 more Smart Citations
“…Muslimov and colleagues recently reported that the mislocalization of BC RNAs is also associated with SLE [38]. Researchers confirmed the production of antibodies that recognize BC200 RNA in SLE patients and named them anti-BC abs.…”
Section: Neuronal Diseases Related To Bc Rnasmentioning
confidence: 94%
“…In 2019, a study by Muslimov et al confirmed that the dendritic localization of BC200 RNA was severely impaired in the autoimmune disease systemic lupus erythematosus (SLE) [38]. They further detected specific antibodies against BC200 RNA in the serum of SLE patients and found that the antibody competitively inhibited binding to hnRNP A2.…”
Section: Regulatory Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…In animal models for both MS and RA, antibodies to A1 and A2/B1, respectively, exacerbate disease. Autoantibodies, including those targeting A1 and A2/B1, have been shown to be internalized within cells of the central nervous system and interact with their intracellular protein targets [ 217 , 218 , 219 ]. MS autoantibodies to A1 in neurons primarily target its M9 nuclear localization sequence [ 210 ], localizing with SGs and trapping A1 in the cytoplasm, and ultimately preventing it from carrying out essential nuclear functions and resulting in neuronal cell death.…”
Section: Hnrnp A1 and A2/b1mentioning
confidence: 99%
“…BC200 (Brain cytoplasmic RNA 1, BCYRN1) is a 200-nt anthropoid primate-specific monomeric Alu RNA that is abundantly expressed in the brain ( 6 , 7 , 8 , 9 ). In a similar manner to its rodent counterpart BC1, BC200 is postulated to regulate localized translation in neuronal dendrites ( 10 , 11 ). BC1 is a 143-nt transcribed ID element, a type of SINE found in variable numbers of copies among rodent species ( 12 ).…”
mentioning
confidence: 99%